Dibenzocyclooctadiene lignans, gomisins J and N inhibit the Wnt/beta-catenin signaling pathway in HCT116 cells - Kang, Kyungsu; Lee, Kyung-Mi; Yoo, Ji-Hye; Lee, Hee Ju; Kim, Chul Young; Nho, Chu Won (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2012)
Here, we report that gomisin J and gomisin N. clibenzocyclooctadiene type lignans isolated from Sch (sonchinensis, inhibit Wnt/beta-catenin signaling in HCT116 cells. Gomisins J and N appear to inhibit Wnt/Bcatenin signaling by disrupting the interaction between beta-catenin and its specific target DNA sequences (TCF binding elements, TBE) rather than by altering the expression of the beta-catenin protein. Gomisins J and N inhibit HCT116 cell proliferation by arresting the cell cycle at the G0/G1 phase. The G0/G1 phase arrest induced by gomisins J and N appears to be caused by a decrease in the expression of Cyclin D1, a representative target gene of the Wnt/beta-catenin signaling pathway, as well as Cdk2, Cdk4, and E2F-1. Therefore, gomisins J and N, the novel Wnt/beta-catenin inhibitors discovered in this study, may serve as potential agents for the prevention and treatment of human colorectal cancers. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: COLON-CANCER CELLS; SCHISANDRA-CHINENSIS; BETA-CATENIN; SUPPRESSES GROWTH; ACTIVATION; COMPONENTS; APOPTOSIS